Identifikasi Keterpaparan Promosi Susu Formula Terhadap Pemberian Asi Eksklusif - Putri Yuliantie; Hairiana Kusvitasari; Frani Mariana (STIKes Payung Negeri Pekanbaru, 2023)
Exclusive breastfeeding is one of the development programs globally. Achieving the target of the Indonesian government on exclusive breastfeeding means helping the world in the success of the goals of the SDGs. The goal that is most closely related to exclusive breastfeeding is SDGs goal number two, namely hunger. the failure of exclusive breastfeeding is influenced by various factors, one of which is by consuming formula milk. The rise of formula milk advertisements has caused many mothers to think that formula milk is not just food, but also medicine for children. This is believed by mothers who have less knowledge about breastfeeding who think that formula milk is better than breast milk because it is practical and contains important nutrients stated in formula milk advertisements.The aim of this study was to identify the exposure of formula milk promotion to exclusive breastfeeding. The research design is an analytic survey with a cross-sectional approach. The population in this study were 159 mothers whose babies were 6-12 months old in the working area of the Sleman Health Center. The results of the statistical test of bivariate analysis of education level p-value 0.808, employment status p-value 0.001 and exposure to formula milk promotion p-value 0.813.